STAGE COSTUME FEATURES ENSEMBLE BAHOR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article reveals the features of costume design of mass and solo dance compositions of the ensemble Bahor. The dances of the ensemble Bahor, and with them their costume design, became an aesthetic canon, a classic of Uzbek choreographic art. The basic principle in creating the costume became an organic unity with a dance design. In the costumes of the ensemble Bahor, persistent signs of a traditional womens costume are preserved, such as ensemble completeness, layering, ethnic jewelry decor, and the brightness of color. At the same time, the costume of each dance has its own look, reflecting the artistic image of the choreographic composition.